(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The study attempts to look into the effect of reference groups on different consumers/shoppers concerning organized retail stores. The study investigates the impact of customers’/shoppers’ attitudes towards purchasing organized retail outlets and the impact of reference groups of different retail sales centers on their participation perspectives. Several studies have examined the location (private and public) of reference groups for firms’ retail outlets. However, research on the impact of reference groups for organized retail outlets is lacking. Also, the influence of strangers to buy the view of the visitor and the participation of customers/buyers in various organized retail stores has been ignored. Conducting empirical research with 539 respondents who are interested in buying different products using social identity theory and analyzing research using structural equation modeling, the results reveal that individual groups influence organized retail outlets and consumer buying indent/consumer. The survey found that public groups and strangers influence consumer/buyer visits to organized retail stores, and reference groups influence purchase intent and customer/buyer behavior at assembled retail stores.